Development, validation and optimisation of a vHTS protocol for identification of estrogen receptor modulators - Knox, Andrew J. S. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2006)
The discovery of small-molecule drugs has reached a critical point in time where the number of new drugs released to market has become static regardless of the technological advances observed over the last few years. ‘Big-pharma’ companies had estimated they would release three to tlve drugs per year annually from 2000 onwards, however the average remains less than one. Methods for drug discovery over the past decades have generally involved the synthesis of compounds selected by an intuitive medicinal chemist, however, a move towards a more rational approach has occurred with the concomitant increase in the number of highly resolved protein structures publicly available. One approach, Virtual High Throughput Screening (vHTS), takes advantage of the rational process by extracting information about the active site of a receptor or enzyme from a protein database and prioritises molecules most likely to bind to the chosen target from a large database of compounds (<1,000,000). When successfully applied, a subset of active compounds may be retrieved by numerous methods in the context of vHTS, namely, 2D/3D descriptors, 2D/3D pharmacophores, QSAR and receptor-based docking.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin